MATHEMATICAL MODEL OF 3D POSITIONING FOR SEAFLOOR DEFORMATION MONITORING - UMMAYA (NIM 15108067); Pembimbing: Dr. Ir. Irwan Meilano, M.Sc., dan Dr. Ir. Dina Anggraeni Sa, RISKA
The deformation measurement is important for observation of dynamics of the earth and many effects from that movement which happen under the seafloor. Electromagnetic waves cannot penetrate sea water into seafloor, therefore seafloor geodetic deformation measurement use combination of kinematic GPS and underwater acoustics observation. Many factors must be considered to obtain precise seafloor position in tectonic deformation observation. Those factors are the methods and processing data in the form of mathematical model. The methods are differential method and Scripps Institution of Oceanography (SIO) method. Trandsponder is identified as a target of deformation in differential method. In the SIO method case, many transponders surround deformation’s target as a virtual area. The objective of this research is to analyze the mathematical model and compare the residuals of the definitive position with the result of mathematical model’s computation. Based on results, SIO method is better and more effective to monitor seafloor geodetic deformation. Mathematic model as a basic of the processing data has many corrections that are systematic error due to time delay of transponder, systematic error due to sound velocity structure cause of internal wave effect, and random error.